Binding of Bacillus thuringiensis proteins with brush border membranes vesicles of the digestive tract of the Andean potato weevil Premnotrypes vorax (Coleoptera: Curculionidae) - MARTÍNEZ, ﻿WILSON; CERÓN-S., JAIRO (Revista Colombiana de Entomología, 2004)
The use of Bacillus thuringiensis as a biological pest control agent requires basic studies related to its mode of action in the selected target insect. Tochniques such as the use of brush border membrane vesicles (BBMV) obtained from epithelial gut tissues of insects have become a valuable tools around the world for studying this mechanism in Bacillus thuringiensis proteins. The objective of this work was to analyze the binding of Cry3Aa, 3Ba, 3Bb, 3Ca and 7Aa B. thuringiensis proteins to BBMV obtained from the digestive tract of Premnotrypes vorax Hustache, in order to explore their potential as biological control agents for this economically important pest in Colombian potato crops. This work was carried out in the Instituto de Biotecnología at the Universidad Nacional de Colombia. Purification of BBMV and protein labeling with biotin were carried our according to methods previously standardized by the authors. Binding assays showed that while Cry3Aa, Cry3Bb and Cry3Ca bind to P. vorax BBMV, Cry3Ba and Cry7Aa did not; however, binding was never correlated with toxicity to first instars of the target insect. Protein blot analysis showed the presence of two possible binding proteins of 70 and 97 KDa, respectively, being the first report made for this endemic pest of the Colombian Andean zone.